Factors Affecting Chemical Variability of Essential Oils: a Review of Recent Developments - Barra, A.
This review, covering mainly papers of the last decade, focuses on recent findings on the different factors affecting the chemical composition of essential oils, such as exogenous and endogenous factors. The endogenous factors are related to anatomical and physiological characteristics of the plants and to the biosynthetic pathways of the volatiles, which might change in either the different tissues of the plants or in different seasons, but also could be influenced by DNA adaptation. The exogenous factors, over a long period, might affect some of the genes responsible for volatiles formation. Those factors lead to ecotypes or chemotypes in the same plant species. In the last few years chemotaxonomy has been widely used to classify plants with essential oils characterized by intra-specific chemical polymorphism. It could be evidenced that chemotypes are frequently genotypes and recently the application of the Random Amplified Polymorphic DNA (RAPD)markers, coupled with powerful statistical methods, appeared to be useful in discriminating the different genotypes. The data presented led to the suggestion that further chemotaxonomic studies should be the result of the analysis of morphological traits combined both with chemical and molecular markers.
Keywords: ESSENTIAL OILS; CHEMICAL VARIABILITY; CHEMOTYPE; GENOTYPE; CHEMOTAXONOMY